Toxicologic Pathology Forum*: Commentary on "Opinion on Designation of Adverse and Nonadverse Histopathological Findings in Toxicity Studies: The Pathologist's Dilemma". (July 2019) - Patrick, Daniel J.; Troth, Sean P.
In the article "Opinion on Designation of Adverse and Nonadverse Histopathological Findings in Toxicity Studies: The Pathologist's Dilemma, " the authors Gopinath and Mowat provide a framework for designation of adversity supplemented with photomicrographic examples. Given that adversity designation can significantly impact the no observed adverse effect level and clinical trial design, it is important to carefully consider all of the criteria by which such assignments are made. We highlight some of the specific assertions within the article that could benefit from a more detailed discussion. Our primary criticism surrounds the authors' primary reliance on histopathology in isolation for adversity designation, which in our opinion provides an overly simplified depiction of the process. We provide additional perspective on how context beyond histopathology often plays a critical role in adversity designation and highlight areas where inclusion of some of these scenarios would have provided the reader a more realistic view of the complex process of assigning adversity. * This is an opinion article submitted to the Toxicologic Pathology Forum. It represents the views of the authors. It does not constitute an official position of the Society of Toxicologic Pathology, British Society of Toxicological Pathology, or European Society of Toxicologic Pathology, and the views expressed might not reflect the best practices recommended by these Societies. This article should not be construed to represent the policies, positions, or opinions of their respective organizations, employers, or regulatory agencies.